2016
DOI: 10.1021/acs.analchem.6b02386
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Natural Products

Abstract: Current mass spectrometry, nuclear magnetic resonance spectroscopy, and X-ray diffraction are presented as structure elucidation tools for analytical chemistry of natural products. Discovering new molecular entities combined with dereplication of known organic compounds represent prerequisites for biological assays and for respective applications as pharmaceuticals or molecular markers. Liquid chromatography is briefly addressed with respect to its use in mass spectrometry- and nuclear magnetic resonance-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 99 publications
0
42
0
2
Order By: Relevance
“…For example, it is well-established that the structure elucidation of an unknown natural product is greatly facilitated by combining the unique information from NMR ( e.g., chemical shifts, coupling constants, NOEs, spin systems, etc. ) with MS ( e.g., exact mass [molecular formula], molecular fragments) [32, 33]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is well-established that the structure elucidation of an unknown natural product is greatly facilitated by combining the unique information from NMR ( e.g., chemical shifts, coupling constants, NOEs, spin systems, etc. ) with MS ( e.g., exact mass [molecular formula], molecular fragments) [32, 33]. …”
Section: Introductionmentioning
confidence: 99%
“…This is an unfortunate and unavoidable outcome of our limited knowledge of the metabolome (the exact composition is currently unknown), the severe limitations in the software and databases available for metabolite identification, and the routine reliance on a single analytical method. Despite the routine application of NMR and MS to elucidate the structures of natural products for drug discovery [32, 33], most metabolic studies still rely on only NMR or MS spectral data for metabolite identification based on database searches [63]. Unfortunately, metabolic databases only contain, at most, a few thousand reference NMR or MS spectra of known metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Characterisation of antimicrobial compounds extracted from TLC‐DB plates was accomplished using GC‐MS in addition to LC‐MS and NMR to potentially enhance detection of heat‐labile and non‐volatile compounds . GC‐MS analysis revealed that the antimicrobial fractions were mixtures of several compounds.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the content of sesquiterpenes possessing an ( E,E)‐ 1,5‐cyclodecadiene structure in Vepris unifoliolata EO was underestimated by GC due to thermal rearrangement . Both liquid chromatography coupled with MS (LC‐MS) and proton ( 1 H) nuclear magnetic resonance (NMR) spectroscopy are conducted at ambient temperature, potentially improving detection of heat‐labile and non‐volatile components . However, these techniques are less commonly employed than GC‐MS in EO analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The accurate determination of molecular mass supported by the corresponding isotope pattern is a widely used mass spectrometry approach for summary formula determination . The experimental isotope pattern is compared to the theoretical pattern calculated from an in silico ‐generated formula.…”
Section: Introductionmentioning
confidence: 99%